History of violence and subjective health of mother and child: From The Childbirth and Health Cohort Study in Primary Care, Iceland. (1st October 2016) - Tomasdottir, Margret O.; Kristjansdottir, Hildur; Bjornsdottir, Amalia; Getz, Linn; Steingrimsdottir, Thora; Olafsdottir, Olof A.; Sigurdsson, Johann A.
Abstract: Objective: To study the self-reported prevalence of experienced violence among a cohort of women about two years after giving birth, their health during pregnancy, pregnancy outcomes and their experience of their child's health. Setting and subjects: In 2011, a total of 657 women participated in phase III of the Childbirth and Health Cohort Study in Icelandic Primary Health Care, 18 to 24 months after delivery. The women had previously participated in phase I around pregnancy week 16 and phase II 5–6 months after delivery. Data were collected by postal questionnaires. Main outcome measures: Women's reported history of experienced violence, sociodemographic and obstetric background, self-perceived health, the use of medications and their child's perceived health. Results: In phase III, 16% of women reported experiencing violence. These women felt less support from their current partner ( p < 0.001), compared to those who did not report violence. Their pregnancies were more frequently unplanned ( p < 0.001), deliveries more often by caesarean section ( p < 0.05), and their self-perceived health was worse ( p < 0.001). They reported more mental and somatic health complaints, and their use of antidepressant drugs was higher ( p < 0.001). Furthermore, women with a history of violence considered their child's general health as worse ( p = 0.008). Conclusions: Our study confirms that a history of violence is common among women. A history of violence is associated with various maternal health problems during and after pregnancy, a higher rate of caesarean sections and maternal reports of health problems in their child 18–24 months after birth. KEY POINTS: Violence is a major concern worldwide. Understanding the impact of violence on human health and developing effective preventive measures are important elements of any public health agenda. The reported prevalence of experiencing violence was 16% among women attending antenatal care in the primary health care setting in Iceland. Women with a history of violence reported worse health in general during pregnancy and delivered more often by caesarean section, compared to women with no such history. Mothers with a history of violence also evaluated the general health of their child as worse than women with no such history. The findings of this study support the importance of recognizing and addressing experienced violence among women in primary care.